Circulating maternal chimeric cells have an impact on the outcome of biliary atresia - Masuya, Ryuta; Muraji, Toshihiro; Kanaan, Sami B.; Harumatsu, Toshio; Muto, Mitsuru; Toma, Miki; Yanai, Toshihiro; Stevens, Anne M.; Nelson, J. Lee; Nakame, Kazuhiko; Nanashima, Atsushi; Ieiri, Satoshi (Frontiers in Pediatrics, 2022)
Introduction We aimed to quantify the DNA of maternal chimeric (MC) cells in the peripheral blood of the BA patients and investigated the impact on the outcome. Method Patients with progressive jaundice because of no bile flow, which necessitated liver transplantation, or who showed inadequate bile flow with or without episodes of cholangitis and progressive hepatic fibrosis and portal hypertension were classified into the poor group. Those with adequate bile flow with completely normal liver function tests beyond two years were classified into the good group. The qPCR were separately carried out in buffy coat samples and plasma samples, targeting the non-inherited maternal HLA alleles in the DNA samples. Results MC-DNA was present in the buffy coat (10–328 gEq per 10^6 host cells) in seven patients. There was no MC-DNA in the remaining five patients. MC-DNA (214 to 15331 gEq per 10^6 host cells) was observed in the plasma of five patients. The quantity of MC-DNA in the buffy coat showed a significant difference between the two prognostic groups (p=0.018), whereas there was no significant difference in the quantity of MC-DNA in plasma (p=0.205). MC-DNA in the buffy coat was significantly associated with the outcome (p=0.028), whereas MC-DNA in the plasma did not influence the outcome (p=0.56). Conclusions Poor outcomes in BA were correlated with circulating maternal chimeric lymphocytes.